STUDY STRUCTURE OF THREE-COMPONENT POLYMERIC MATERIAL UNDER INFLUENCE OF γ-IRRADIATION - V. T. Tarasyuk; V. P. Filippovich; A. V. Prokopenko; N. E. Strokova; A. V. Egorkin; A. V. Chasovskikh (Теория и практика переработки мяса, 2017)
The polymer material (РА/РЕ/Eva) with a width of 55 μm was studied. Sterilization was carried out on the unit GU–200 at doses from 3 to 18 kGy in the Research Institute of Technical Physics and Automation, Rosatom, Moscow, Russia. The structure of the polymermaterial samples was studied by IR spectroscopy before and after irradiation in a range of 400–5000 сm–1. According to the results of the analysis of the IR spectrum structure, the changes in the structure were insignificant upon irradiation at doses up to 6 kGy. Upon irradiation at doses from 9 kGy and higher, an increase in quantity of ester groups (2340 сm–1) and insignificant increase in other functional groups were observed, which can suggest a simultaneous process of intra-molecular cross-linking with the intermediatestage of cross-linking occurring with formation of vinylene groups. This causes destruction of a polymer material and radiation oxidation. These disorders can lead to changes in physico-mechanical and barrier parameters of a polymer material, which can be notably reflected in the shelf life of agricultural products.